HUBUNGAN KOMPETENSI SOSIAL DAN KOMPETENSI PROFESIONAL GURU DENGAN KINERJA GURU SEKOLAH DASAR DI KECAMATAN CINA KABUPATEN BONE - Rukmina Sari, Rahmah Nita; Sari Achmad, Widya Karmila; Rahman, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the relationship between social competence, professional competence, and the performance of elementary school teachers in Cina District, Bone Regency. The suboptimal performance of teachers in implementing learning remains a phenomenon in elementary schools. Teachers are expected to improve their abilities in carrying out learning tasks, building effective communication and collaboration within the school environment, and developing the competencies required of professional educators. Therefore, this issue needs to be examined scientifically. This study employed a quantitative approach with a correlational research design. The population consisted of all certified teachers, including classroom teachers and subject teachers, totaling 62 teachers. The sample comprised all members of the population selected using total sampling (sensus sampling). Data on teachers’ social competence and professional competence were collected through questionnaires, while teacher performance data were obtained from the documentation of Teacher Performance Assessment (PKG) results available in schools. The findings indicate that teachers’ social competence and professional competence were categorized as very high, while teacher performance was categorized as high. In addition, there was a positive relationship between social competence and teacher performance, between professional competence and teacher performance, and simultaneously between social competence, professional competence, and teacher performance. The study concludes that teacher performance is related to teachers’ social competence and professional competence. Social competence supports effective interaction, communication, and collaboration with students, colleagues, and parents, thereby creating a conducive working environment. Meanwhile, professional competence strengthens teachers’ ability to master learning materials, understand students’ characteristics, and manage the learning process in a planned and systematic manner. Therefore, both competencies are important factors associated with improving teacher performance.